2015
DOI: 10.1007/s00199-015-0900-0
|View full text |Cite
|
Sign up to set email alerts
|

Public debt and total factor productivity

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
(21 reference statements)
1
4
0
Order By: Relevance
“…However, financiers cause the economy to achieve higher economic growth. This outcome is similar to that derived by Kaas (2014) in which low interest rates create lower TFP but lead to greater capital accumulation.…”
Section: Financial Crisissupporting
confidence: 84%
“…However, financiers cause the economy to achieve higher economic growth. This outcome is similar to that derived by Kaas (2014) in which low interest rates create lower TFP but lead to greater capital accumulation.…”
Section: Financial Crisissupporting
confidence: 84%
“…Azariadis and Kaas (2016) shows, for example, that with imperfect capital markets, TFP performs well when equities are owned by productive firms. Similarly, Kaas (2016) argues that a long-run equilibrium can be characterized by the coexistence of low real interest rate and TFP because the less efficient firms succeed in surviving at the lower capital cost. But more recently, Capasso et al (2019) showed that, contrary to simplistic predictions, the real exchange rate can cause the real interest rate in an asymmetric way.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, they show how credit market frictions limit capital mobility and slow down the movement of resources from temporarily less to temporarily more productive sectors, and more generally, from temporarily low to temporarily high valuations. Accordingly, Kaas ( 2016 ) developed a DGE model exploring the role of public debt on TFP. He shows that a stable equilibrium is one in which a reduction of the primary deficit triggers an expansion of credit and capital, however leading to a deterioration of TFP.…”
Section: Literaturementioning
confidence: 99%